2020
DOI: 10.1111/dth.13411
|View full text |Cite
|
Sign up to set email alerts
|

The unforeseen during biotechnological therapy for moderate‐to‐severe psoriasis: How to manage pregnancy and breastfeeding, infections from Mycobacterium tuberculosis , hepatitis B virus, hepatitis C virus, and HIV , surgery, vaccinations, diagnosis of malignancy, and dose tapering

Abstract: The use of biotechnological therapies for moderate‐to‐severe psoriasis is ever‐expanding and it is becoming increasingly more frequent to encounter different unforeseen events during their use, such as fertile patients becoming pregnant and breastfeeding, development of infections due to personal habits like tuberculosis, hepatitis B virus, hepatitis C virus, or HIV, scheduling of surgical procedures, need of vaccinations, development of malignancy, and evaluation of dose tapering. As any clinician may experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
4
1
1
Order By: Relevance
“…Although phototherapy is a recommended and safe treatment option for psoriasis in PLHIV, 16,32 the PLHIV group in our study had a statistically lower rate of phototherapy treatment. As most Thai PLHIV are of working age and have low incomes, 33 leaving work to attend regular intensive phototherapy sessions is problematic.…”
Section: Ta B L E 3 (Continued)contrasting
confidence: 52%
See 2 more Smart Citations
“…Although phototherapy is a recommended and safe treatment option for psoriasis in PLHIV, 16,32 the PLHIV group in our study had a statistically lower rate of phototherapy treatment. As most Thai PLHIV are of working age and have low incomes, 33 leaving work to attend regular intensive phototherapy sessions is problematic.…”
Section: Ta B L E 3 (Continued)contrasting
confidence: 52%
“…As most Thai PLHIV are of working age and have low incomes, 33 leaving work to attend regular intensive phototherapy sessions is problematic. Moreover, none of the PLHIV with psoriasis in the current study received biologics despite there being increasing evidence of their safety profiles for PLHIV 16,32 . This might be because Thailand’s national health system only covers the costs of oral systemic drugs and phototherapy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…should not be started during an active infection because they may potentially give rise to a multitude of infections, so should be contraindicated for HIV patients even if some authors suggested safety modalities for their use. 3,4 Nevertheless, single case reports have shown that treatment with other biologics (such as anti-IL17) or oral small molecules (i.e., apremilast) may be successful and safe in HIVpatients affected by moderate-severe psoriasis. [5][6][7][8][9] Here we describe our clinical experience with an anti-IL17A monoclonal antibody, secukinumab, in an HIV positive psoriatic man who failed an initial treatment with apremilast.…”
mentioning
confidence: 99%
“…However, a substantial body of clinical experiences has shown that TNF-alpha inhibitors and ustekinumab may be safely administered in such special patient population. [1][2][3][4] Recently, a HIV-positive patient treated with the fully human monoclonal antibody anti-IL-17A secukinumab, was reported. 5 Here, we describe a first clinical experience with the IL-17 receptor brodalumab in a HIV-positive psoriatic patient.…”
mentioning
confidence: 99%